A Survey on Teachers’ Perception of Online Learning in the Covid-19 Pandemic - Firharmawan, Hastri (English Education and Literature Journal (E-Jou), 2022)
Since the Covid-19 pandemic online learning has become a technological breakthrough to cope with the learning problems in education. However, the rapidness of the changes in the technology demands teachers to be always updated and adaptive to the development of the new technology. This survey study deals with teachers’ perception of online learning in the Covid-19 pandemic. The perception was seen from three aspects, namely the usefulness, the ease of use, and the attitude toward online learning on English subject. The study employed a descriptive design with qualitative approaches. The samples involved 60 Junior high school English teachers in Kebumen. Questionnaires and interviews were used in order to get data needed from the subjects. The study found that the teachers had a positive perception toward the online learning they had executed in terms of both the usefulness and ease of use. However, more than half of them disagree for the online learning on being effectively used. In relation to the attitude, it was found that the teachers responded positively toward applying new technologies in their online teaching.   Keywords: Online learning, teacher, perception, Pandemic